2013
DOI: 10.3791/50460
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering of a Human 3D <em>in vitro</em> Tumor Test System

Abstract: Cancer is one of the leading causes of death worldwide. Current therapeutic strategies are predominantly developed in 2D culture systems, which inadequately reflect physiological conditions in vivo. Biological 3D matrices provide cells an environment in which cells can self-organize, allowing the study of tissue organization and cell differentiation. Such scaffolds can be seeded with a mixture of different cell types to study direct 3D cell-cell-interactions. To mimic the 3D complexity of cancer tumors, our gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…In an attempt to understand the fundamental principles behind the induction of angiogenesis, development of 3D models investigating the interactions between different cell types has progressed [Mon- , 1993;Donovan et al, 2001;Santos et al, 2008]. Other studies have looked at the influence of fluid flow on EC survival and sprouting [Moll et al, 2013;VukadinovicNikolic et al, 2014]. However, we are unaware of any models that have the ability to combine different cell combinations and fluid flow to investigate the induction of earlystage blood vessel formation for TE applications.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to understand the fundamental principles behind the induction of angiogenesis, development of 3D models investigating the interactions between different cell types has progressed [Mon- , 1993;Donovan et al, 2001;Santos et al, 2008]. Other studies have looked at the influence of fluid flow on EC survival and sprouting [Moll et al, 2013;VukadinovicNikolic et al, 2014]. However, we are unaware of any models that have the ability to combine different cell combinations and fluid flow to investigate the induction of earlystage blood vessel formation for TE applications.…”
Section: Discussionmentioning
confidence: 99%
“…For static culture, vascular grafts were placed in a cell crown culture system consisting of two metal rings according to Moll et al [16] Therefore, sterilized vascular scaffolds were opened on one side, cut in pieces of approximately 1 cm 2 , and placed onto the smaller inner ring of a metal crown. Following, scaffolds were clamped by placing the bigger outer ring above the inner ring.…”
Section: Methodsmentioning
confidence: 99%
“…Discrepancy between our results and the results presented by Eritja and colleagues (Eritja et al, 2010) could be due to the origin and type of endometrial epithelial cells used in the modelling, in which they used normal mouse endometrial epithelial cells whereas we used human endometrial cancer cells. In addition, endometrial epithelial cells modelled in 3D rBM and 3D poly-HEMA systems showed reduced proliferation as compared to cells grown in 2D, which is similar to findings from other groups (Fallica et al, 2012, Moll et al, 2013. Furthermore, in either of these two types of 3D culture systems distinctive phenotypes of MCSs were presented by different endometrial epithelial cell lines, which recapitulate to some extent certain biological features of neoplastic transformation and progression of endometrial epithelial cells.…”
Section: Discussionsupporting
confidence: 84%